Prognostic Role of Sarcopenia in High-grade Lymphoma: A Retrospective PET/CT-Based Study - Özlem Beyler; Yunus Güzel; Cengiz Demir; Serdar Yıldırım; Canan Can; Halil Kömek (Acta Haematologica Oncologica Turcica)
Aim: This study aimed to evaluate the impact of sarcopenia and myosteatosis on progression-free survival (PFS) in patients with aggressive non-Hodgkin lymphoma (NHL). Methods: A retrospective analysis was conducted on 33 high-grade NHL patients diagnosed between 01.01.2018 and 31.12.2019, who had pre- and post-treatment 18F-fluorodeoxyglucose positron emission tomography/computed tomography (CT) imaging. Body composition was semiautomatically measured using axial CT slices at the lumbar L3 vertebral level, focusing on the psoas muscle (PM). The right and left average hounsfield unit (HU) values [right psoas HU corrected (RPHUc) and left psoas HU corrected (LPHUc)] were recorded as myosteatosis parameters. The cross-sectional area of the PM was adjusted for body size by dividing it by the square of the patient’s height in meters, resulting in the PM index, expressed in cm²/m². Results: The average age of the patients was 57±16.2 years, and sarcopenia was identified in 39.4% of the cohort. During follow-up, relapse occurred in 9 patients (27.3%). A significant association was found between relapse and age (p=0.002), Eastern Cooperative Oncology Group (ECOG) performance status (p=0.003), and RPHUc (p=0.015). Receiver operating characteristic analysis for RPHUc (cut-off >33.550) in predicting PFS showed an area under the curve of 0.778 (p=0.015), with 66.7% sensitivity and 33% specificity. Univariate analysis identified age (p=0.001), ECOG score (p=0.000), and RPHUc (p=0.017) as significant prognostic factors for PFS. In multivariate analysis, only age remained an independent prognostic factor (p=0.04). Conclusion: Our study demonstrated that age and RPHUc values have prognostic significance for PFS in aggressive lymphoma patients. These parameters, easily obtainable from routine imaging, may aid in guiding clinical management strategies.